2017
DOI: 10.2166/wh.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation of bacterial water quality and the relationship with pasture land cover

Abstract: Pathogens are a major cause of water quality impairment and public health concern world-wide.In the United States, each state is tasked with developing water quality standards (WQS) to protect the designated use(s) of waterbodies. Several streams in the Illinois River Watershed in northwest Arkansas are currently listed as impaired due to elevated levels of pathogens. Our objective was to evaluate Escherichia coli (E. coli) numbers at 29 stream sites, compare these numbers to the applicable WQS, and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
2
10
0
2
Order By: Relevance
“…The dominant flow conditions might cause the differences in concentrations among sampling locations. Scott et al (2017) noted that during base‐flow conditions, sources of bacteria can be localized because bacteria are less likely to be transported great distances downstream during low flows due to slower water velocities, greater predation, and increased presence of pools and increased settling into the stream bed sediments. Piorkowski et al (2014b) reported significant differences in E. coli concentrations in sediments between those found in riffles and those found in pools, which they attributed to lower velocities and higher settling rates of fine particles, which are associated with E. coli attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant flow conditions might cause the differences in concentrations among sampling locations. Scott et al (2017) noted that during base‐flow conditions, sources of bacteria can be localized because bacteria are less likely to be transported great distances downstream during low flows due to slower water velocities, greater predation, and increased presence of pools and increased settling into the stream bed sediments. Piorkowski et al (2014b) reported significant differences in E. coli concentrations in sediments between those found in riffles and those found in pools, which they attributed to lower velocities and higher settling rates of fine particles, which are associated with E. coli attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados mostraron también un patrón de densidad máxima de E. coli en el tramo Medio de los cauces periurbanos caracterizados como BDF mejor conservados. Patrones similares fueron publicados en otros trabajos (Collins, 2004;Scott et al, 2017). Para Collins (2004) las altas densidades de bacterias reflejan la fracción desproporcionadamente grande del flujo superficial y subsuperficial de la cuenca que pasa a través de los humedales y, por tanto, actúan como sumideros de microorganismos.…”
Section: La Abundancia Bacteriana Y El Metabolismo Fluvial En Los Bañunclassified
“…Approaches to protect riparian seep areas include riparian fencing, off‐stream water sources, stream crossings, riparian buffers, and grazing management (Agouridis et al ; Swanson et al ). Although relationships with riparian pasture cover and increased E. coli have been documented (Scott et al ), limited studies have evaluated seep E. coli transport in pasture lands (Collins and Rutherford ). Collins and Rutherford () developed a model to simulate E. coli and used field measurements to illustrate elevated E. coli inputs from seepage areas accessed by cattle (10 4 to 10 8 MPN) during base flow and rain events.…”
Section: Seeps As Contaminant Sourcesmentioning
confidence: 99%